Osteoporosis Related Knowledge and Attitudes: The Scenario in Tripoli, Libya - AR, Abduelkarem; AM, Hamrouni; MM, Alhmadi; AM, Tawati (Journal of Medical Biomedical and Applied Sciences, 2019)
Background: Osteoporosis is a worldwide disease, which is characterized by a reduction in bone mass and alteration of its architecture that increases bone fragility and the risk of fracture. Objective: This study aimed to assess knowledge and attitudes towards osteoporosis of undergraduate medical students in Libya. Methods: A cross sectional-based study was conducted at Tripoli University, Libya among medical undergraduate students. The participants’ responses were encoded and descriptive analysis was undertaken, and the chi-squared test was used to ascertain any significant difference among the participants’ responses. Results: More than half (389; 52.1%) of the respondents from three different medical colleges have had some knowledge about osteoporosis. More than three quarters (576; 77.1%) described osteoporosis as brittle bones. The majority, 676 (90.5%) agreed with the statement that women are more likely to get osteoporosis than men. Regarding the knowledge of participants about the link between osteoporosis and other health indicators/conditions, the majority 638 (85.4%) of the respondents did not agree that “osteoporosis is a non-hereditary disease”. Interestingly, 486 (65.1%) of the participants did not agree that osteoporosis affects women only at menopause, and that smoking, alcohol drinking, and pollution were an important risk factors in developing osteoporosis. In reducing the risk of osteoporosis, 725 respondents (97%) selected calcium and 617 (82.6%) selected vitamin D as important nutrients. Conclusions: Medical university students have acceptable but not comprehensive knowledge about osteoporosis related to epidemiology, etiology, pathophysiology and treatment. There is need to continuously revise the medical colleges syllabi and update the courses to reflect recent advances in the management of osteoporosis.